Before nature : a Christian spirituality - Santmire, H. Paul (Minneapolis.: : Fortress press, 2014)
Before Nature caps a set of themes first brought to the fore in Santmire's previous work, most notably the classic The Travail of Nature. Here Santmire continues the pursuit of a theology bound up with nature and its condition, especially the fragility and fervent expectation of nature's redemption. Out of this concern, Santmire invites readers on a theological and spiritual journey to a prayerful and contemplative knowledge of the Triune God, in which practitioners are inducted into a bountiful relationship with the cosmic and universal ministry of Christ and the Spirit uniting all of nature in a single vision of hope and anticipation. Scholarly, practical, and accessible.
A Christian spirituality of nature for today's seekers and their teachers and pastors -- Blessedly scything with God: you are invited -- Introducing a way of prayer: the practice and the knowing of the Trinity prayer -- The world in which we pray: the eclipse of God and a fragile theology of faith -- Praying to Jesus: the revelation of God and the light of Christ -- The ambiguous case of one who prays to Jesus: the twilight and the encounter -- The heart of the Trinity prayer: contemplating the mystery of the Triune God -- The presence of the Triune God in nature: contemplating God in all things -- The works of the Triune God in nature: contemplating the cosmic ministries of Jesus Christ and the Holy Spirit -- Calling on the Holy Spirit: the integrity and the travail of nature -- Sauntering in the Spirit: practicing the Trinity prayer -- The Trinity prayer as spiritual exercise.
Includes bibliographical references and index.
Keywords: Nature -- Religious aspects; Human ecology -- Religious aspects; Ecotheology